2018
DOI: 10.1089/rej.2017.1989
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Mitochondrial DNA at the Crossroads of Mitochondrial Dysfunction and Inflammation During Aging and Muscle Wasting Disorders

Abstract: Mitochondrial structural and functional integrity is maintained through the coordination of several processes (e.g., biogenesis, dynamics, mitophagy), collectively referred to as mitochondrial quality control (MQC). Dysfunctional MQC and inflammation are hallmarks of aging and are involved in the pathogenesis of muscle wasting disorders, including sarcopenia and cachexia. One of the consequences of failing MQC is the release of mitochondria-derived damage-associated molecular patterns (DAMPs). By virtue of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 111 publications
(139 reference statements)
2
88
0
1
Order By: Relevance
“…As SIRT1 has a role in regulating oxidative metabolism and connecting global metabolism to longevity and regeneration, we also examined mitochondrial subpopulations to identify potential differences in these subpopulations resulting from variant SIRT1 expression. Mitochondrial dysfunction may be a fundamental component that regulates aging responses along several pathways . Previous work has suggested that IFM and SSM subpopulations are affected differently in cardiac muscle by diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…As SIRT1 has a role in regulating oxidative metabolism and connecting global metabolism to longevity and regeneration, we also examined mitochondrial subpopulations to identify potential differences in these subpopulations resulting from variant SIRT1 expression. Mitochondrial dysfunction may be a fundamental component that regulates aging responses along several pathways . Previous work has suggested that IFM and SSM subpopulations are affected differently in cardiac muscle by diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are double membrane‐bound organelles responsible for energy production. Mitochondrial integrity is maintained through the coordination of several processes such as biogenesis and mitophagy, which have been collectively referred to as mitochondrial quality control (MQC) . Dysfunctional MQC and inflammation are key signatures of ageing and several ageing‐related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial integrity is maintained through the coordination of several processes such as biogenesis and mitophagy, which have been collectively referred to as mitochondrial quality control (MQC). 17 Dysfunctional MQC and inflammation are key signatures of ageing and several ageing-related diseases. As part of the mitochondrial energy generating process involving the electron transport chain (ETC), high-energy electrons leak and generate reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dysfunctional mitochondrial quality control and neuroinflammation have been considered to be at the crossroads of ageing and muscle wasting disorders. In particular, mitochondria‐derived damage‐associated molecular patterns have been specifically implicated in experimental sarcopenia and cachexia models …”
Section: Pathophysiologymentioning
confidence: 99%
“…In particular, mitochondriaderived damage-associated molecular patterns have been specifically implicated in experimental sarcopenia and cachexia models. 63 However, our comprehensive literature search found that the current body of evidence mainly concerns cachexia associated with cancer, end-stage pulmonary disease, heart failure, and renal failure. Therefore, there is a knowledge gap in regarding cachexia and dementia, and our understanding of the pathophysiological background is currently based on mere extrapolation from these other findings.…”
Section: Mitochondrial Dysfunction and Oxidative Stressmentioning
confidence: 99%